Black, white, and Indian : race and the unmaking of an American family - Saunt, Claudio (Oxford University Press, 2005)
This tells the story of a Native American family with a long kept secret: one branch is of African descent. Focusing on five generations from 1780 to 1920, Saunt shows how Indians disowned their black relatives to survive in the shadow of the expanding American republic.